The Influence of Service Quality, Brand Image, and Online Customer Reviews on Purchase Decisions - Kuncoro, Bagus Tri; Suharti, Suharti (Economics and Business International Conference Proceeding, 2024)
The purpose of this study was to analyze the effect of service quality, brand image, and online customer reviews on purchasing decisions (shopee application) for FEB students at Muhammadiyah University Semarang. the population in this study were consumers who wanted to buy products in the shopee application, the number of which was known with certainty. The sampling technique used non-probability sampling where the sample did not provide an opportunity to be selected as a sample member, sampling by accidental sampling. the number of samples was determined using the slovin formula, totaling 95 respondents. Based on the results of the spss test, it shows that the service quality variable (x1) has a positive and significant effect on purchasing decisions (y), brand image (x2) has a positive and significant effect on purchasing decisions (y), online customer review (x3) has no positive and significant effect on purchasing decisions (y), then simultaneously and together it can be concluded that service quality, brand image, and online customer review have a positive and significant effect on purchasing decisions.